Insights into the menstrual cycle : exploring menstrual cycle patterns in healthy New Zealand women : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Auckland, New Zealand - Bowler, Tyler (Massey University, 2025)
Background: Poor understandings of the female reproductive cycle and its variability within and between women have led to ambiguity when considering ‘normal’ characteristics and features of the menstrual cycle. While the evidence base in female reproductive health is growing, there is minimal research assessing the features and characteristics of the menstrual cycle in healthy, naturally menstruating, premenopausal women, particularly over numerous consecutive cycles. Therefore, the primary objective of this study was to assess the characteristics of the menstrual cycle in healthy New Zealand women across three to five cycles. A secondary aim was to determine the individual and lifestyle factors that may influence the presence of ovulatory disturbances. Methods: This prospective cohort study assessed 97 healthy females over three to five consecutive menstrual cycles. A three-step method was used to collect menstrual cycle data, and included calendar-based counting, urinary luteinising hormone (LH) testing and plasma steroid hormone measurement. Presence of subclinical ovulatory disturbances (SOD), including anovulation and luteal phase defects (LPD), was assessed and classed using mid-luteal plasma progesterone thresholds. Women were assigned an ovulatory status based on whether they experienced two or more ovulatory cycles (ovulatory status) or two or more SOD cycles (SOD status). Individual and lifestyle data were collected using demographic, menstrual cycle history and physical activity questionnaires. Descriptive statistics were used to determine menstrual cycle features (menstrual cycle, menses, ovulation, follicular and luteal phase length). A linear mixed model was used to determine the within-woman and between-women variability of phase lengths across ovulatory status. A logistic regression including gynaecological age, total metabolic equivalent physical activity and percentage body fat was used to establish demographic and anthropometric associations with SODs. Results: In this study, 74.1% of menstrual cycles were ovulatory, 13.5% were anovulatory, and 12.4% were LPD. In women who contributed at least two cycles of data, 34.9% experienced sporadic SOD cycles, and 8.1% experienced recurrent SOD cycles. In cycles in which ovulation occurred, the average day of ovulation was day 14, and day 13 for LPD cycles. The sporadic incidence of SOD cycles was found to be associated with age and gynaecological age, but not body composition, ethnicity, or level of physical activity. Within-woman variability of menstrual features was found to be greater in SOD women than in ovulatory women. Significant differences in menstrual cycle and luteal phase length between ovulatory and SOD cycles were detected. Conclusion: Overall, while the majority of menstrual cycles are ovulatory, the presence of SODs, including anovulatory and LPD cycles, are relatively common in healthy, naturally menstruating women. Of note, sporadic SOD cycles appear to be more common than recurrent SOD cycles. While ovulatory cycles tend to follow normative expectations of a menstrual cycle, women who frequently experience SOD cycles may experience more menstrual cycle variability. Future research should expand on the findings of the current study and examine the presence of SOD cycles within longitudinal studies in order to better capture the between-women and within woman variability.
Keywords: 321004 Nutritional science